2010
DOI: 10.1002/kpm.343
|View full text |Cite
|
Sign up to set email alerts
|

New product development for a food and beverage company: A showcase of evidence‐based management

Abstract: We develop a model of new product development which may inform decision-making on innovation and knowledge management in this paper. The new model combines extant theoretical framework and actual practice from a leading Food and Beverage chain in Hong Kong to illustrate how evidence-based management (EBM) can be practiced in new product development. Some salient features of the model include generating new ideas constantly, improving success rate of new ideas, and ensuring collaboration among internal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Suppliers of raw materials for the R&D department obtained the best evaluation scores, which was different from other destinations. These results highlighted the importance of the R&D department of the foil producer in conducting its own research [ 28 , 61 ]. The necessity of having an R&D department is aimed at conducting own research in the fields of control and improvement of current products and the development of new ones [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppliers of raw materials for the R&D department obtained the best evaluation scores, which was different from other destinations. These results highlighted the importance of the R&D department of the foil producer in conducting its own research [ 28 , 61 ]. The necessity of having an R&D department is aimed at conducting own research in the fields of control and improvement of current products and the development of new ones [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The necessity of having an R&D department is aimed at conducting own research in the fields of control and improvement of current products and the development of new ones [ 3 ]. It could be not without significance that the foil producer operates in a country, where the economic development level, measured by GDP per capita, was below average while the share of actively innovation-driven companies was above average [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation studies mean that models used in different fields should be handled in developing new products in restaurants. Man, Lui, and Lai (2010) were conducted by testing a model called Evidence-Based Management (EBM), which is generally applied in education and medicine, on a food and beverage business. Findings showed that the model in question could be used in developing new products.…”
Section: New Product Development In Restaurantsmentioning
confidence: 99%